Keamanan Penggunaan Antiglukolan pada Pasien Rawat Inap Stroke Iskemik dengan Atrial Fibrilasi - Juniarto Mende; Fita Rahmawati; Ika Puspitasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Atrial fibrillation can cause stroke due to blood stasis in the left atrium which triggers thrombus formation and embolization of the brain. Administration of anticoagulants is used to prevent clot formation to prevent the occurrence of stroke, but on the other hand, it is associated with the risk of bleeding side effects. This study aims to evaluate the safety of anticoagulants in ischemic stroke patients with atrial fibrillation. The study used a cross-sectional design. Retrospective data were taken from the medical records of RSUP Dr. Sardjito, Yogyakarta period January 2018 to December 2020. The research subjects were ischemic stroke patients with atrial fibrillation. Evaluation of the safety of anticoagulants includes the number of major and minor bleeding events in each type of anticoagulant and the factors that influence the occurrence of bleeding. A total of 70 patients met the study inclusion criteria. Bleeding occurred in 41 cases (58,57%). Major bleeding was 28 patients (40%) and minor bleeding was 13 patients (18,57%). The most common anticoagulant that causes bleeding is warfarin. Multivariate test of the factors that influence the occurrence of bleeding in kidney failure (OR = 5,990; 95% Cl 2,002-17,920; p = 0,001). Monitoring the side effects of anticoagulants, especially warfarin is necessary. Pharmacists can play an important role in monitoring and preventing bleeding events by taking into account risk factors, especially kidney failure.